Autophagy transduces physical constraints into biological responses. (October 2016) - Dupont, Nicolas; Codogno, Patrice
Abstract: Autophagy is a fundamental cell biological process that controls the quality and quantity of the eukaryotic cytoplasm. Dysfunctional autophagy, when defective or excessive, has been linked to human pathologies ranging from neurodegenerative and infectious diseases to cancer and inflammatory diseases. Autophagy takes place at basal levels in all eukaryotic cells. The process is stimulated during metabolic, genotoxic, infectious, and hypoxic stress conditions and acts an adaptive mechanism essential for cell survival. Recent data demonstrate that changes in the mechanical cellular environment influence cell fate through the modulation of the autophagic pathway. Mechanical stimuli, such as applied forces, combine with biochemical signals to control development and physiological functions of different organs and can also contribute to the progression of various human diseases. Here we review recent findings regarding the regulation of autophagy upon three types of mechanical stress, compression, shear stress, and stretching, and discuss the potential implications of mechanical stress-induced autophagy in physiology and physiopathology.